Communication Strategies in the Written Medium: The Effect of Language Proficiency - Aliakbari, Mohammad; Allvar, Nabi Karimi (Linguistik Online, 2009)
Although much has been written on ’communication strategies’ (CS), in the sense of potentially conscious plans for solving problems encountered in reaching particular communicative goals, there still remain large gaps in our knowledge in this respect. One area worthy of attention, and not totally clarified, is whether these strategies are applied and workable in writing as frequently as they are in speaking tasks. Accordingly, the present study aimed at pitting the use of CS against language proficiency level in argumentative writing of Iranian university students. The results of the Chi-Square tests run for the purpose of investigating the hypotheses showed that language proficiency was highly related with the use of more Reconceptualization Strategies which are thought to be psycho linguistically more demanding compared with Substitution Strategies.